Thyronamine regulation of TAAR1 expression in breast cancer cells and investigation of its influence on viability and migration - Tremmel E (Dove Medical Press, 2019)
Eileen Tremmel,1 Simone Hofmann,1 Christina Kuhn,1 Helene Heidegger,1 Sabine Heublein,2 Kerstin Hermelink,1 Rachel Wuerstlein,1 Nadia Harbeck,1 Doris Mayr,3 Sven Mahner,1 Nina Ditsch,1 Udo Jeschke,1 Aurelia Vattai1 1Breast Center, Department of Gynecology and Obstetrics and CCC Munich, University of Munich (LMU), 81377 Munich, Germany; 2Department of Gynecology and Obstetrics, University of Heidelberg, 69120 Heidelberg, Germany; 3Department of Pathology, Ludwig-Maximilians University of Munich, 81337 Munich, Germany Objectives: A correlation exists between breast cancer and thyroid disorders, which are common in elderly women. Thyroid hormones are degraded into trace amines, which can bind to the G-protein-coupled receptor trace amine-associated receptor 1 (TAAR1) and thereby activate it. The transformation of thyroid hormones into trace amines is carried out by the ornithine decarboxylase. Previously, we showed that TAAR1 overexpression (IRS ≥6) was associated with a significantly longer OS in primary breast cancer patients during a long-term follow-up of up to 14 years. Aim of the present study was to analyze the regulation of TAAR1 in breast cancer cell lines and the influence of triiodothyronine (T3), thyronamines, and tetraiodothyroacetic acid (Tetrac) on the expression of TAAR1 in breast cancer cells. Methods: The effect of T3, thyronamines, and Tetrac on the expression of TAAR1 in breast cancer cell lines MCF-7 and T47D was analyzed via PCR and Western blot. A MTT assay was performed to test the metabolic cell viability. A scratch assay was performed to analyze cell migration. Results: Stimulation of MCF-7 cells with 10 nM 3-iodothyronamine (T1AM) significantly increased TAAR1 protein expression (P=0.008). In T47D cells, TAAR1 expression was significantly upregulated after the addition of 10 µg/mL estradiol to 10 nM T1AM (P=0.008). A significant (P=0.028) reduction in MCF-7 cell viability through the incubation with T1AM could be detected. Cell migration of MCF cells was significantly reduced through incubation with 10 nM T1AM. Conclusion: A significant upregulation of TAAR1 induced by stimulation with T1AM may be a sign for an increased decarboxylation of thyroid hormones in breast cancer cells. In addition, there seems to be an influence of estradiol for the T1AM-induced upregulation of TAAR1 in T47D cells. TAAR1-related cell transduction mechanisms seem to be an interesting target for endocrine treatment options of breast cancer patients. Keywords: breast cancer, TAAR1, 3-iodothyronamine, Tetrac, MCF7, T47D